The Mosque as the Centre of the Islamic Political Movement: Uncovering Al-Faruqi's Strategic Vision in the Contemporary Era - Nur Khalim, Ahmad Dwi (Dirasah: Jurnal Pendidikan Islam, 2025)
The role of mosques as centers of community activity has experienced a decline in the modern era, becoming limited to ritualistic functions without addressing the social-political needs of the Muslim community. This contrasts with the early history of Islam, where mosques were hubs for social transformation, education, and politics. In the modern context, challenges such as secularism, materialism, and low political awareness among Muslims underscore the urgency of revitalizing mosques as spaces for Islamic political education. This study aims to analyze Ismail Raji al-Faruqi’s concept of tawhid as a strategic foundation for political education in mosques, exploring its potential to cultivate a generation of Muslims aware of their political and social responsibilities. Using a qualitative-descriptive approach based on library research, the findings indicate that mosques have significant potential to become inclusive spaces that integrate the values of tawhid with principles of social justice, solidarity, and equality. Al-Faruqi’s thought emphasizes that mosque-based Islamic political education not only counters secularism and materialism but also fosters a harmonious and just society. However, challenges remain in fully utilizing mosques as political spaces, making their revitalization a strategic step to restore their historical function as centers for both spiritual and social-political empowerment.